Periploca forrestii Saponin Ameliorates Murine CFA-Induced Arthritis by Suppressing Cytokine Production - Yingqin Liu; Minghui Li; Qiuhong He; Xinping Yang; Fang Ruan; Guangchen Sun (Mediators of Inflammation)
Periploca forrestii Schltr. has been used as a Chinese folk medicine due to its versatile pharmacological effects such as promoting wounds and rheumatoid arthritis. However, the antiarthritic activity of Periploca forrestii saponin (PFS) and its active compound Periplocin has still not been demonstrated. Here, we evaluated the antiarthritic effects of PFS in adjuvant-induced arthritis (AIA) rats by intragastric administration at a dose of 50 mg/kg. The anti-inflammatory activities of Periplocin were also examined in LPS-induced AIA splenocytes and synoviocytes. PFS significantly ameliorated joint swelling; inhibited bone erosion in joints; lowered levels of IL-6 and TGF-β1 in AIA rat splenocyte; and reduced joint protein expression levels of phospho-STAT3 and IKKα. Using LPS-induced AIA splenocytes, we demonstrate that Periplocin suppressed the key proinflammatory cytokines levels of IL-6, IFN-γ, TGF-β1, and IL-13 and IL-22 and transcription factor levels of T-bet, GATA3, and C-Jun genes. Periplocin also suppressed LPS-induced cytokine secretion from synoviocytes. Our study highlights the antiarthritic activity of PFS and its derived Periplocin and the underlying mechanisms. These results provide a strong rationale for further testing and validation of the use of Periploca forrestii Schltr. as an alternative modality for the treatment of RA.